Reward systems and employee performance: examining the impact in organizational settings - Meta Amelia Putri; Hendri Ardianto; Andi Prayoga (Ifma Publishing, 2026)
The increasing demands for productivity in the food industry require companies to optimally manage their human resources. One key factor believed to drive employee performance is the reward system. This study aims to analyse the impact of the reward system on employee performance in companies operating within the food sector. The methodology employed is a quantitative survey involving 85 employees, selected through total sampling techniques. Data were collected using a five-point Likert scale questionnaire and analysed using descriptive and inferential statistics through simple linear regression with the assistance of SPSS version 24 at a significance level of 0.05. The results indicate that the reward system has a positive and significant effect on employee performance. The better the reward system implemented, the higher the level of performance exhibited by employees. These findings underscore the importance of a fair and structured reward system as a managerial strategy to enhance work productivity within the food industry.